2000
DOI: 10.1046/j.1365-2133.2000.03831.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in dermatological outpatients: an issue to be recognized

Abstract: Our study has depicted the situation that is actually faced by dermatologists in their everyday practice, where they are in a unique position to recognize psychiatric morbidity and to take appropriate measures. The GHQ-12, being easy for patients to compile and for physicians or nurses to score, may be a practical tool to increase identification of patients with substantial psychological distress or formal psychiatric disorder in order to provide more comprehensive and appropriate intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
312
7
30

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(387 citation statements)
references
References 32 publications
38
312
7
30
Order By: Relevance
“…In another study, psychiatric morbidity was found more frequent in women and singles than men and married people (26). In our study, psyhcopathology was found more frequent in women than men which is consistent with literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In another study, psychiatric morbidity was found more frequent in women and singles than men and married people (26). In our study, psyhcopathology was found more frequent in women than men which is consistent with literature.…”
Section: Discussionsupporting
confidence: 82%
“…In several studies, psychiatric disorders were reported to be observed more in people with dermatological diseases (23)(24)(25)(26)(27)(28). In a study done in cases with vitiligo, 40% of cases were found to be depressive and had low self-esteem (29).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous psychological/psychiatric conditions can be found in association with SISL, but in most cases 3 groups are encountered: adjustment disorders, depressive disorders and personality disorders [3]. The frequency of emotional disorders in dermatological patients has been reported to range between 25.2% and 33.4% [7][8][9]. The prevalence of psychosomatic disorders among patients with skin problems is three times higher in comparison with somatically healthy control cohorts [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Medical intervention therefore, can make a big difference to such patients either by complete clearing or causing significant improvement of the condition. 20 The main principles of treatment of acne consist of elimination of comedones by normalization of follicular keratinization, decreasing sebaceous gland activity and reduction in the population of P. acne and thereby reducing the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%